1996
DOI: 10.1007/bf02172520
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and physical mapping inBrassica diploid species of a gene cluster defined inArabidopsis thaliana

Abstract: We report the genetic and physical analysis by pulse field gel electrophoresis (PFGE) in three Brassica diploid genomes for a cluster of five genes characterized in a selected segment of 15 kb on chromosome 3 of Arabidopsis thaliana, encoding a Bradyrhizobium CycJ homologue (At1), a rat p67 translation factor homologue (At2), an Em-like (early methionine) protein (At3), chlorophyll synthase (At4) and a yeast Sac1 homologue (A5). The Arabidopsis gene array was found to be conserved on a single linkage group in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 31 publications
2
23
1
Order By: Relevance
“…However, a significant proportion (11 of 16 or 68%) of markers that were single-copy in Arabidopsis were also single-copy in Brassica. This result differs from previous Brassica and Arabidopsis comparative mapping studies in which single-copy Arabidopsis markers were found to be duplicated in the Brassica genome (Lagercrantz et al, 1996;Sadowski et al, 1996). …”
contrasting
confidence: 99%
See 2 more Smart Citations
“…However, a significant proportion (11 of 16 or 68%) of markers that were single-copy in Arabidopsis were also single-copy in Brassica. This result differs from previous Brassica and Arabidopsis comparative mapping studies in which single-copy Arabidopsis markers were found to be duplicated in the Brassica genome (Lagercrantz et al, 1996;Sadowski et al, 1996). …”
contrasting
confidence: 99%
“…All three markers also hybridized consistently with a 780-kb SfiI fragment that is, in all likelihood, a partially digested fragment (incomplete digestion is often observed upon treatment of Brassica DNA with SfiI; Sadowski et al, 1996). Marker y14 hybridized with the same 510-and 780-kb SfiI fragments as did the HV8 probe and with the same 97-kb BssHII and 115-kb SmaI fragments as did sp400.…”
Section: Comparative Mapping Of Molecular Markers In Arabidopsis and mentioning
confidence: 75%
See 1 more Smart Citation
“…Initial efforts at determining the relationships between the Brassica and Arabidopsis genomes involved using molecular probes for co-linear sets derived from the developing Arabidopsis genomic resources to map RFLP polymorphisms in Brassica species (Kowalski et al, 1994). These studies indicated that there is extensive co-linearity between the Brassica and Arabidopsis genomes, but that most single copy Arabidopsis regions exist as multiple, on average 3 copies in modern Brassica genomes (Lagercrantz et al, 1995;Sadowski et al, 1996;Cavell et al, 1998). This in turn, gave rise to the hypothesis that the modern diploid Brassica species are derived from a hexaploid ancestor whose genome was generated from a diploid, Arabidopsis-like genome through polyploidization events.…”
Section: Brassica Genomesmentioning
confidence: 99%
“…oleracea and A. thaliana diverged 15-20 million years ago (Yang et al 1999). Earlier comparative mapping studies of Brassica and Arabidopsis using molecular markers revealed extensive synteny between these two species, suggesting that knowledge gained in one species can be productively applied to the other (Lan et al 2000;Babula et al 2003) although deviation from colinearity was also noted (Kowalski et al 1994;Sadowski et al 1996;Ryder et al 2001). Nucleotide sequence conservation between these two species has been reported to be in the range of 75%-90% in exons, whereas in introns and intergenic regions, it is Յ70% .…”
mentioning
confidence: 99%